Pemodelan Penggunaan E-Money Pada E-Parking Kota Makassar - Ihsan, Hisyam; Side, Syafruddin; Wulandari, Emi (Jurusan Matematika FMIPA UNM, 2020)
This study aims to build a model of the use of E-Money in E-Parking type SIRI (Susceptible - Infected - Recovered - Infected) in Makassar City. The added assumption is that people who have used E-Money can may return to cash payments on parking. This model is divided into three classes, namely vulnerable / potentially using parking, cash users, and E-Money users. The data used are primary data obtained by direct survey in the field. The survey was conducted by distributing questionnaires to 100 respondents randomly. The SIRI type mathematical model is used to determine the equilibrium point. The simulation results of the SIRI type model produce a base reproduction number (R0) of 0.021021 which means that the use of cash can decrease which causes the use of E-Money will increase in a certain period of time.